Strength and durability performance of acid-mechanically treated recycled aggregate concrete with metakaolin, lime powder, and A-fine - Chauhan B.L.; Singh G.J.; Kumar A.; Kumar R. (My University, 2025)
This study examines the effectiveness of lime powder (LP) and metakaolin (MK) in concrete containing acid-mechanically treated recycled concrete aggregate (RCA). The acid-mechanically produced recycled fine, i.e., A-Fine (AF), is also evaluated as a supplementary cementitious material (SCM). According to the strength activity index (SAI) for AF, it has a low pozzolanic reactivity in comparison to MK and a higher pozzolanic reactivity in comparison to LP. An optimal dosage of AF (15 %), LP (17 %), and MK (22 %) improves the physical properties of recycled aggregate concrete (RAC). The compressive strength of RAC with AF (RAC-AF) is closer to that of RAC with LP (RAC-LP), and RAC with MK (RAC-MK). As a result of their partial or complete chemical inertness, AF, LP, or MK decrease the self-cementing capability of RCA and reduce the mechanical properties and fracture energy of RAC. While the split tensile and flexural strength of RAC-AF is greater than that of RAC-LP, it is smaller than that of RAC-MK. As a result of their higher elastic modulus, RAC-AF and RAC-MK are more ductile than RAC and RAC-LP. As a result of low ion penetration and high electrical resistance, RAC, RAC-AF, RAC-LP, and RAC-MK are classified as low permeability materials. AF or MK as a cement substitute does not alter the sorptivity of RAC despite improvement. In contrast, RAC has higher initial and final absorption when LP substitutes for cement. According to their pozzolanic reactivity and filler effect, RAC sorptivity varies with these SCMs. There is a strong correlation between the compressive strength and UPV of RAC, RAC-AF, RAC-LP, and RAC-MK with R2 = 0.94. The sorptivity and electrical resistivity are also correlated with R2 = 0.94. Due to the formation of Si-rich C-S-H gels, SEM and EDS show a more uniform and denser microstructure in RAC-AF, RAC-LP, and RAC-MK. © 2024 Elsevier Ltd